The Impact of Energy Consumption, Economic Freedom and Corruption on Manufacturing Performance: Panel Data Evidence from Low-Income Sub-Saharan African - Hassan, Sallahuddin; Danmaraya, Ismail Aliyu (2017)
This paper examines the causal link concerning manufacturing performance, institutional quality and energy consumption for pane of five middle-income countries in Sub-Saharan Africa (Botswana, Nigeria, Senegal, Sudan & South Africa) for the period 1995-2012.The panel co-integration test displays evidence of co-integration among the variables. The result of the Fully Modified OLS pointed out that energy consumption, labour and capital formation are important factors that determines manufacturing performance in the five middle-income SSA countries while corruption variable and economic freedom are not significant in determining the performance of the manufacturing sector. Equally, the result revealed causality running from manufacturing performance to energy consumption, capital formation and economic growth as well as bidirectional causality between manufacturing performance and labour and, between manufacturing performance and corruption variable.The study therefore suggests that energy conservation policy will have less negative effect on manufacturing performance.